THE IMPACT OF ONLINE GAMBLING ADDICTION ON ADOLSELCENTS’ EMOTIONAL AND BEHAVIORAL CONDITIONS - Putri, Nabila Ade; Marcella, Agis; Patricia, Kethlyn; Yustitia Tri Putri, Erinda; Okta Sari, Resti (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2024)
This study aims to identify and analyze the emotional impact of online gambling addiction on adolescents, including conditions such as anxiety, depression, and stress. It also explores how online gambling addiction can affect adolescents’ behavior, including changes in social interactions, academic performance, and daily living patterns. The results showed that online gambling addiction has a significant impact on adolescents’ emotional state and behavior, with internal (lack of desire to play) and extreme (peer environment and lack of parental control) factors as the main causes. This study recommends early intervention to prevent such problems and raise public awareness about the risks of online gambling.